Effectiveness Of Using The Wondershare Quiz Creator-Based Quiz On Understanding Concept In Calculus I - Farman Farman (Unversitas Muhammadiyah Mataram, 2020)
Abstract: This study aims to determine the effectiveness of giving quizzes based on wondershare quiz creators on students' ability to understand concepts in the Calculus I course. This research is an pre-experimental study with one group pretest-posttest design. This study's population were all students of the Sembilabelas November Kolaka University Mathematics Education Study Program in the 2018/2019 academic year. The sample of this research is a saturated sample which is used as an experimental class with a total of 46 students. Data were analyzed descriptively and inferential with paired sample t-test with the SPSS application with a significance level of 0.05. The results showed that: (1) the average ability of students' concept understanding was in the medium category with an average of 70.66. (2) Learning by giving quizzes based on wondershare quiz creator is effectively applied in the Calculus I course to support students' conceptual understanding skills.Abstrak: Penelitian ini bertujuan untuk mengetahui efektivitas pemberian kuis berbasis wondershare quiz creator terhadap kemampuan pemahaman konsep mahasiswa pada mata kuliah Kalkulus I. Penelitian ini merupakan penelitian pre-eksperimen dengan desain penelitian one group pretest-posttest design. Populasi penelitian ini adalah seluruh mahasiswa Program Studi Pendidikan Matematika Universitas Sembilabelas November Kolaka tahun akademik 2018/2019. Sampel penelitian ini adalah sampel jenuh yang dijadikan sebagai kelas eksperimen dengan jumlah sebanyak 46 mahasiswa. Data dianalisis secara deskriptif dan inferensial dengan uji-t sampel berpasangan (paired sample t-test) dengan aplikasi SPSS taraf signifikansi 0,05. Hasil penelitian diperoleh bahwa: (1) rerata kemampuan pemahaman konsep mahasiswa telah berada pada kategori sedang dengan rarta-rata mencapai 70,66. (2) Pembelajaran dengan pemberian kuis berbasis wondershare quiz creator efektif diterapkan dalam matakuliah Kalkulus I untuk mendukung kemampuan pemahaman konsep mahasiswa.